2011
DOI: 10.3109/15563650.2011.609822
|View full text |Cite
|
Sign up to set email alerts
|

Severe Toxicity Following Synthetic Cannabinoid Ingestion

Abstract: Objective To report a case of seizures and supraventricular tachycardia (SVT) following confirmed synthetic cannabinoid ingestion. Background Despite widespread use of legal synthetic cannabinoids, reports of serious toxicity following confirmed use of synthetic cannabinoids are rare. We report severe toxicity including seizures following intentional ingestion of the synthetic cannabinoid JWH-018 and detail confirmation by laboratory analysis. Case Report A healthy 48 year old man had a generalized seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 24 publications
5
141
2
4
Order By: Relevance
“…In the same study, a 60-year-old man with a 40-year history of cannabis usage (6-8 cigarettes per day) developed status epilepticus after cannabis withdrawal [225]. Additionally, synthetic "designer" cannabinoid drugs ("spice" or "K2") induce new-onset seizures, tacharrythmia, and psychosis, often with greater severity and toxicity than cannabis [237][238][239][240][241][242][243][244][245]. The toxicity of these synthetic agents may result from their properties as full agonists of CB 1 R, while Δ9-THC is a partial agonist.…”
Section: Case Studiesmentioning
confidence: 95%
“…In the same study, a 60-year-old man with a 40-year history of cannabis usage (6-8 cigarettes per day) developed status epilepticus after cannabis withdrawal [225]. Additionally, synthetic "designer" cannabinoid drugs ("spice" or "K2") induce new-onset seizures, tacharrythmia, and psychosis, often with greater severity and toxicity than cannabis [237][238][239][240][241][242][243][244][245]. The toxicity of these synthetic agents may result from their properties as full agonists of CB 1 R, while Δ9-THC is a partial agonist.…”
Section: Case Studiesmentioning
confidence: 95%
“…Given the high abundance of CYP2C9 in the intestine, it is anticipated that this isoform will be intricately involved in the intestinal metabolism of synthetic cannabinoids taken orally, as well as other routes of exposures. Consideration of oral routes of exposure is important because we have previously shown that ingestion of JWH-018 can lead to rapid and severe toxicity in humans (Lapoint et al, 2011). Toxic drug-drug interactions are also an important concern for public health officials, especially because hepatic intrinsic clearance associated with CYP2C9 metabolism is greater than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas use of cannabis, which contains the natural psychoactive cannabinoid ⌬ 9 -tetrahydrocannabinol (⌬ 9 -THC), is often associated with mild symptoms such as appetite stimulation and orthostatic hypotension (Jones, 2002;Randall et al, 2004), K2 users present to emergency departments with severe adverse effects including hypertension, visual and auditory hallucinations, tachycardia, sinus bradycardia, chest pain, dysrhythmias, seizures, psychosis, intracranial hemorrhage, and even death (Mü ller et al, 2010;Vearrier and Osterhoudt, 2010;Benford and Caplan, 2011;Every-Palmer, 2011;Lapoint et al, 2011;Schneir et al, 2011;Simmons et al, 2011a,b;Young et al, 2011;Pant et al, 2012). In addition, recent medical reports indicate that chronic K2 use may lead to the development of tolerance, dependence, and withdrawal (Zimmermann et al, 2009), as has been observed with marijuana abuse (Budney and Hughes, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Her initial vital signs were HR 82 bpm, BP 117/61 mm Hg, RR 20/min, SpO 2 96% on room air (RA), and temperature 99. 5 F. She left the hospital AMA after her initial blood draw. She did not receive any other interventions before she left the ED, and after her departure her laboratory results were reported to be within normal limits.…”
Section: Initial Epidemiological and Law Enforcement Investigationmentioning
confidence: 99%
“…Reports of cases and outbreaks of unpredicted, severe toxicity have increased as the number of SCs introduced to the market has risen. Seizures are one of the most common unpredictable toxicities reported after SC exposure (4)(5)(6)(7)(8)(9)(10). Chest pain and cardiovascular toxicity after SC use have also been reported (11,12).…”
Section: Introductionmentioning
confidence: 99%